The PRISM4 (mid-Piacenzian) palaeoenvironmental reconstruction - Dowsett, Harry; Dolan, Aisling; Rowley, David; Pound, Matthew; Salzmann, Ulrich; Robinson, Marci; Chandler, Mark; Foley, Kevin; Haywood, Alan (Copernicus, 2016)
The mid-Piacenzian is known as a period of relative warmth when compared to the present day. A comprehensive understanding of conditions during the Piacenzian serves as both a conceptual model and a source for boundary conditions and means of verification of global climate model experiments. In this paper we present the PRISM4 reconstruction, a palaeoenvironmental reconstruction of the mid-Piacenzian (~ 3 Ma) containing data for palaeogeography, land and sea-ice, sea-surface temperature, vegetation, soils and lakes. Our retrodicted palaeogeography takes into account glacial isostatic adjustments and changes in dynamic topography. Soils and lakes, both significant as land surface features, are introduced to the PRISM reconstruction for the first time. Sea-surface temperature and vegetation reconstructions are unchanged but now have confidence assessments. The PRISM4 reconstruction is being used as boundary condition data for the Pliocene Model Intercomparison Project, Phase 2 (PlioMIP2) experiments.